A clean self-diverting acid for carbonate reservoir in deep wells at high temperatures and its performance evaluation - Xiangsen Gao; Min Wang; Xian Shi; Bin Li; Jian Mao; Poplygin Vladimir Valerievich (Scientific Reports)
Abstract The key technology for stimulating carbonate oil and gas reservoirs lies in the meticulous selection of an appropriate acid system, control over the action distance of active acid on the reservoir, and attainment of good conductivity through non-uniform etching of the rock wall surface by acid. Currently, retarded acid systems are beset by serious acid filtration problems, resulting in a limited length of acid-etched fractures and incomplete polymer breakage of glue in residual acids after stimulation, ultimately impeding oil and gas reservoir production and efficiency. In response to the development requirements of high-temperature deep hydrocarbon reservoirs, a clean diverting acid system based on VES surfactant has been successfully developed. Through systematic evaluation of key parameters including temperature-viscosity characteristics, filtration performance, retardation efficiency, friction reduction capability, and intelligent viscosity-altering mechanism, experimental results demonstrate: Under conditions of 170 s−1 shear rate and 160 °C, the system maintains a dynamic viscosity ≥ 50 mPa·s, representing a 14.3% improvement in temperature resistance compared to current diverting acid systems (with a general temperature resistance limit of 140 °C). The filtration coefficient measures 2.08 × 10−4 m/min0.5 (equivalent to 26% of that of conventional retarded acids), with a flow friction coefficient of 0.25 (75% reduction compared to the water baseline). The friction reduction efficiency shows a 41.7% enhancement over traditional diverting acids (30% friction reduction rate). Furthermore, its viscosity range is narrower than that of traditional viscosity-modifying acids, preventing excessive filtration of the acid solution and increasing the reservoir stimulation volume. The innovative clean self-diverting acid fulfills all requirements for deep acid fracturing in deep high-temperature oil and gas reservoirs with complex geological characteristics.